(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
The real time application of an embedded Linux is essential in the area of device driver platform. Device driver plays a vital role of both hardware and software. For making these terms in bridge connectivity for the purpose of reliable data transfer Multi-tasking is most important to run the task in perfect scheduling process with a minimized time. Kernel module requires initial boot loader for time requirement here start up time is more important. Execution parameter for hardware is reliable model, Here above model has been done by Beagle bone black board.